2017
DOI: 10.1038/s41598-017-13086-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial functional genes elucidate environmental drivers of biofilm metabolism in glacier-fed streams

Abstract: Benthic biofilms in glacier-fed streams harbor diverse microorganisms driving biogeochemical cycles and, consequently, influencing ecosystem-level processes. Benthic biofilms are vulnerable to glacial retreat induced by climate change. To investigate microbial functions of benthic biofilms in glacier-fed streams, we predicted metagenomes from 16s rRNA gene sequence data using PICRUSt and identified functional genes associated with nitrogen and sulfur metabolisms based on KEGG database and explored the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 89 publications
(88 reference statements)
0
29
0
Order By: Relevance
“…Glacier-fed streams and lakes reflect the integration of both upstream and in situ processes (Figure 1; Brittain and Milner, 2001;Mindl et al, 2007;Robinson et al, 2016;Hotaling et al, 2017b;Ren and Gao, 2019). Melting glaciers supply key water, sediment, and nutrients to aquatic ecosystems, determining their optical properties, resource availability, and the structure and composition of biological communities (Laspoumaderes et al, 2013;Martyniuk et al, 2014;Rose et al, 2014;Hotaling et al, 2017b;Ren et al, 2017a ; Figures 4, 5). In general, glacier-fed streams and lakes are characterized by considerable sediment input from upstream grinding of bedrock, cold temperatures (e.g., < 10 • even in summer), and dynamic water levels.…”
Section: Living Downstream Of Ice: Glacier-fed Streams and Lakesmentioning
confidence: 99%
“…Glacier-fed streams and lakes reflect the integration of both upstream and in situ processes (Figure 1; Brittain and Milner, 2001;Mindl et al, 2007;Robinson et al, 2016;Hotaling et al, 2017b;Ren and Gao, 2019). Melting glaciers supply key water, sediment, and nutrients to aquatic ecosystems, determining their optical properties, resource availability, and the structure and composition of biological communities (Laspoumaderes et al, 2013;Martyniuk et al, 2014;Rose et al, 2014;Hotaling et al, 2017b;Ren et al, 2017a ; Figures 4, 5). In general, glacier-fed streams and lakes are characterized by considerable sediment input from upstream grinding of bedrock, cold temperatures (e.g., < 10 • even in summer), and dynamic water levels.…”
Section: Living Downstream Of Ice: Glacier-fed Streams and Lakesmentioning
confidence: 99%
“…As high-elevation headwaters, alpine streams are a key hydrological link between cryospheric processes and downstream habitats, both freshwater and marine (Hood, Battin, Fellman, O'Neel, & Spencer, 2015;Hotaling, Hood, et al, 2017;O'Neel et al, 2015). To date, most studies of microbial ecology in alpine headwaters have emphasized ice-fed streams, and particularly those fed by surface glaciers (Freimann et al, 2013a;Ren, Gao, Elser, & Zhao, 2017;Wilhelm et al, 2013) with rare rock glacier examples (Fegel et al, 2016). However, there has been considerably less focus on other stream types (but see Esposito et al, 2016), and no comparisons across multiple stream types in the same geographic region have been made.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, high proportions of positive correlations between nodes in the two networks suggested the interdependencies among bacterial taxa under environmental disturbance. Topological parameters provide important information to help us to understand microbial community structure 2,3,47,52 . Higher values of network centralization and heterogeneity in the emerged areas than in the inundated areas suggested that there were many tightly connected bacterial modules (subnetworks in the whole network) in the emerged areas.…”
Section: Discussionmentioning
confidence: 99%
“…S2c). In general, ANR processes are much more prevalent than DNR processes in natural ecosystems 3,71 , and high concentrations of NH 4 + could stimulate assimilatory pathways 67,71,72 . The reduction processes of NO 3 − to NO 2 − and then to NH 4 + are part of the ANR processes, which usually occur in anaerobic environments such as sediment and soil 73 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation